Health Promotion with a Resource-advantage Based Theory Towards P-Care Services Excellent - Lusianti, Dina; Rahmawati, Noor; Ni’am, Infijarun (Yayasan Meira Visi Persada, 2025)
The scarcity of competitive resources poses a challenge for first-level health facilities in delivering health services, which can impact the quality of health promotion. This study aims to develop a health promotion model based on the Theory of Resource-Based Competitive Advantage, integrated with the value of religiosity. Through a literature study, this research found that humanist resources, unique resources, and the reconfiguration of technological resources integrated with religious values will have an impact on delivering excellent service, which leads to mastery of market positions. Competition between health facilities to provide mutual benefit to JKN Participants is not necessarily to seek world benefits alone. The support of the first-level health facilities will contribute to the sustainability of the JKN program.